The mechanism underlying lexical selection: Evidence from the picture–picture interference paradigm - Geng, Jingyi (Q J Exp Psychol (Hove), 2013)
In two experiments using the picture–picture and picture–word interference paradigms, we compared predictions from the swinging lexical network and the response exclusion hypothesis to determine whether the process of word selection is competitive. Further, we suggest that previous categorical effects in the picture–picture interference paradigm were due to stimuli confounds, thus readdressing the debate concerning categorical effects in the paradigm. Consistent with both hypotheses, in Experiment 1 we found faster picture naming times when distractor pictures were associatively related than when they were unrelated, explained as a result of a spread of activation at the conceptual level with little (swinging lexical network) or no (response exclusion hypothesis) contribution from lexical competition. In Experiment 2, we found a significant categorical interference effect in the picture–word interference paradigm, and this effect significantly decreased but was not facilitatory when distractors were pictures. We discuss how these results are consistent with the swinging lexical network and conclude that the process to select a word is a competitive one.